Gut Microbiota and Fecal Metabolites Associated With Neurocognitive Impairment in HIV-Infected Population - Dong, Ruihua; Lin, Haijiang; Chen, Xiaoxiao; Shi, Ruizi; Yuan, Shiying; Li, Jing; Zhu, Bowen; Xu, Xiaohui; Shen, Weiwei; Wang, Keran; Shu, Xiao-Ou; Ding, Ding; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Gut microbiota dysbiosis has been associated with many neurological diseases. However, how microbiota composition and metabolism relate to neurocognitive impairment (NCI) in HIV-infected individuals is largely unknown. In this study, a total of 102 HIV infected participants, were classified into two groups—those with NCI and those without, using the global deficit score (GDS). Faecal samples were collected from participants for 16S rRNA gene sequencing and untargeted metabolomics. Plasma level of 25 hydroxy-vitamin D (25(OH)D) was also evaluated. Although α-diversity and β-diversity were comparable, HIV patients with NCI were significantly different from those without NCI in abundance of several gut microbiota. The decreased abundance of butyrate-producing bacteria (BPB) and increased abundance of Klebsiella were related with NCI and carotid intima-media thickness (CIMT). Significant differences in faecal metabolites were also found between individuals with versus without NCI, including increased bile acids and bioactive lipids, decreased vitamin D, terpenoids and Resolvin D1 in the NCI group. Furthermore, the perturbed metabolic profile was closely related to BPB and Klebsiella. In addition, low level of vitamin D was associated with NCI and CIMT. Both faecal and plasma vitamin D were positively correlated with BPB. Our results show BPB and Klebsiella and associated metabolites are associated with NCI in people with HIV. In addition, vitamin D, both in feces and blood, was associated with NCI and BPB, suggesting a protective effect of vitamin D on NCI.